EDITORIAL - Sayyid M. Syeed (International Institute of Islamic Thought, 1991)
We report with great sadness the death of Victor Danner, a friend of Islam and Muslims, a graduate of Georgetown and Harvard, and Chairman of the Department of Near Eastern Languages and Cultures at Indiana University, BloomingtOn, Indiana. Darner's latest publication was The Islamic Traditiontion : An Introduction. W have been inviting Muslim anti non-Mush scholars from time to time to present their responses to the International Institute of Islamic Thought’s caIl for the Islamization of Knowledge. So far, we have been very lucky to have had the opportunity to listen to the late Fazlur Rahman, Sayyed H. Nasr, Abdulaziz Sachedina and others who joined this debate at the IIIT headquarters. Some of these responses have been published in various issues of AJISS. Victor Danner treated us to his response on May 15, 1989, when he presented his paper, which appears in this issue under the title of “Western Evolutionism in the Muslim World,” at the IIIT headquarters. In this article, he launches an eloquent plea for the rediscovery and reexploration of the various schools of thought in Islam and their subsequent adaptation to the needs and circumstances faced by contemporary Muslims. He reminds us that past attempts at reform by Muslim intellectuals were based on a readaptation of the traditional techniques of Islam which, when presented in a fresh manner as a solution to the needs faced by their own contemporaries, gave the doctrine of tawhid “a powerful radiance that had a convincing allure to it.” This is followed by an examination of the origins of evolutionary thinking in the West, how its eventual acceptance and spread throughout the West ultimately displaced Christian beliefs and institutions on a massive scale, and how the resulting secular civiIization produced by it is threatening to sweep aside and destroy traditional Islamic civilization. In closing, he states his hope that a better understanding of this phenomenon among the Muslim intelligentsia and the people at large will cause them to wake up to this danger and begin to work for the preservation of the ”traditional culture of Islam.” Our first article in this issue is by Imaduddin Khalil, and addresses the Qur’an’s relationship vis-his modem science. After ruling out the Qur’an as a book or textbook of scientific knowledge, he proceeds to discuss the philosophy and aims of science and the basic principles of Islam. He begins with the role of humanity on earth as the khaEfuh of Allah, moves on to the principles of tawazun (balance) and taskhir (an Islamic concept stating that the world and nature have been made subservient to humanity), and closes with the principle of a link between creation and the Creator. Khalil views the Qur’anic methodology as being a “methodology of discovery” of ...